2011
DOI: 10.1016/j.yexcr.2011.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Migration of connective tissue-derived cells is mediated by ultra-low concentration gradient fields of EGF

Abstract: The directed migration of cells towards chemical stimuli incorporates simultaneous changes in both the concentration of a chemotactic agent and its concentration gradient, each of which may influence cell migratory response. In this study, we utilized a microfluidic system to examine the interactions between Epidermal Growth Factor (EGF) concentration and EGF gradient in stimulating the chemotaxis of connective-tissue derived fibroblast cells. Cells seeded within microfluidic devices were exposed to concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 42 publications
2
53
0
Order By: Relevance
“…In addition, the Chemotactic index, CI, was used as the measure of directed cell migration, as defined in Eq. (2) (Kong et al, 2011): CI=xd where x is distance toward gradient and d is total accumulated distance. Values approach 1 as cells move more directly toward the gradient, are negative for cells moving away from the gradient.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the Chemotactic index, CI, was used as the measure of directed cell migration, as defined in Eq. (2) (Kong et al, 2011): CI=xd where x is distance toward gradient and d is total accumulated distance. Values approach 1 as cells move more directly toward the gradient, are negative for cells moving away from the gradient.…”
Section: Methodsmentioning
confidence: 99%
“…However, it remains to be clarified whether the EGF/EGFR system affects the multipotency of PDL-derived undifferentiated mesenchymal cells. On the other hand, Kong et al reported that EGF positively controls migratory activity of bovine medial collateral ligament-derived fibroblasts [21]. However, it remains to be elucidated what kinds of molecular mechanisms underlie the proliferation, migration, and MF differentiation of the PDL-derived undifferentiated fibroblastic cells.…”
Section: Introductionmentioning
confidence: 99%
“…15 Another study has demonstrated that transactivation of EGF-R via PDGFR-B activity was able to guide MB migration in vivo . 2 Further, EGF-mediated migration has been shown to be concentration gradient-dependent, as breast cancer cells, 32 fibroblast cells 21 and glioma cells 1 responded to increasing gradients of EGF via higher motility in vitro .…”
Section: Introductionmentioning
confidence: 99%